Peranan Konseling Dosen Wali dalam Meningkatkan Motivasi Belajar Mahasiswa di Perguruan Tinggi Swasta (Jurnal Bimbingan dan Konseling Islam, 2020)
Counseling in Higher Education is clearly an indispensable activity after the teaching system becomes a semester credit system, which requires students to arrange and plan their own credit collection program every semester as effectively as possible. Counseling activities in educational institutions or in everyday social life are functional activities or services that are professional or expertise on the basis of science and technology. Counseling is a conscious effort of one component of our education, given that counseling is an activity of assistance and demands given to individuals in general and students or students in particular in the context of the world of education. According to Pepinsky (in Shertzer & Stone, 1974) counseling is an interaction that (a) occurs between two individuals, each called a counselor and client (b) occurs in a professional atmosphere (c) is carried out and maintained as a tool to facilitate change changes in behavior Students who are studying in a tertiary institution that they meet every day after the family is a university or campus environment. This research was conducted by taking a sample of students from the Private Higher Education Region of LLDIKTI IV. The method used is descriptive analysis method with 83 respondents, the target outputs in the form of national journals received